Position sensitivity of optical nano-antenna arrays on optoelectronic devices. (November 2018) - Hou, Chaojian; Wang, Yang; Yang, Lijun; Li, Bo; Cao, Ziqing; Zhang, Qihan; Wang, Yaqiong; Yang, Zhan; Dong, Lixin
Abstract: Optical nano-antennas (ONAs) are designed for enhancing light-harvesting efficiency in wireless transmission of optical energy and/or signals, which are of great interests in photodetection or solar energy conversion, particularly in micro-/nanoscale systems such as micro-/nanorobots, implantable sensors, and nanoelectromechanical systems, where self-power is not readily available due to a too small volume of the system itself. A critical challenge for the integration of ONAs is how to rationally place ONAs at the "sweetest" regions in the photoactive devices for more effective photodetection or photovoltaics, which offset the application of ONAs in optoelectronic devices. Here, we exploit a near-infrared pentamer ONAs arrays taking few-layer molybdenum disulfide (MoS2 ) as photodetectors to investigate the effect of common locations of ONAs on photocurrent amplification. We show that additional photocurrent amplification (larger than 60% in our devices) can be achieved by placing ONAs close to the depletion regions, i.e., the interface between functional elements and one of the metal electrodes, demonstrating the strong position sensitivity of ONAs on optoelectronic devices. Additionally, the maximum photoresponsivity of few-layer MoS2 photodetectors under the wavelength of 830 nm had been achieved up to 250 mA/W based on the optical filed enhancement and absorption modulation of MoS2 nanosheets with our near-infrared pentamer ONAs, indicating its application for near-infrared photodetection. Finally, the maximum responsivity of MoS2 -based nanodevice with pentamer ONA arrays ( 0.111 mA/W) under self-powered conditions is enhanced by a factor of 7 as against MoS2 -based nanodevice without pentamer ONA arrays. These findings are expected to be valuable for the development of more efficient light-harvesting schemes for both optoelectronic devices and implantable or in-body micro-/nanosystems. Graphical abstract: fx1 Highlights: Pentamers-shaped optical nanoantennas (ONAs) are fabricated with 15-nm gaps between Au disks. MoS2 photodetectors are placed beneath an array of ONAs to investigate their position sensitivity. The responsivity of MoS2 photodiodes with ONAs is up to 0.111 mA/W; 7 times better than without ONAs. The optimal position of ONAs is close to the inner side of an electrode around the depletion regions. Locally positioning ONAs close to the optimal site, an extra photocurrent > 60% is achieved.